2022
DOI: 10.1177/10497323221110356
|View full text |Cite
|
Sign up to set email alerts
|

How Culture Shapes Informal Caregiver Motivations: A Meta-Ethnographic Review

Abstract: The provision of informal care presents a significant global challenge. To better understand how cultural factors underpin and shape motivations and willingness to provide informal care for adults, an in-depth qualitative synthesis was conducted. Six electronic databases and a wide range of additional sources were searched. Following meta-ethnographic guidelines, 37 qualitative studies were synthesised. Six main concepts were identified: cultural self-identity, which appeared as an overarching explanatory conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 95 publications
1
8
0
Order By: Relevance
“…Apart from the limitations mentioned above, the Bahasa Indonesia version of DFPS possesses initial evidence of factorial validity (Azwar, 2013), thus can be used to explore the relationship between filial piety and other variables related to parent-child relationship dynamics. Previous studies have shown the role of reciprocal and authoritarian filial piety in elderly parents' caregiving, such as caregiving motivation or burden (e.g., Pan et al, 2022;Zarzycki et al, 2022). Parental caregiving is a common practice in Indonesian society, where adult children live with their parents or in-laws after marriage.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the limitations mentioned above, the Bahasa Indonesia version of DFPS possesses initial evidence of factorial validity (Azwar, 2013), thus can be used to explore the relationship between filial piety and other variables related to parent-child relationship dynamics. Previous studies have shown the role of reciprocal and authoritarian filial piety in elderly parents' caregiving, such as caregiving motivation or burden (e.g., Pan et al, 2022;Zarzycki et al, 2022). Parental caregiving is a common practice in Indonesian society, where adult children live with their parents or in-laws after marriage.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, not all OSGs consider the gender, racial, cultural, or faith-based background of participants, which may impact the efficacy of the support [ 74 ]. Motivations for caregiving can be influenced by cultural underpinnings, such as filial piety, familism, and repayment and reciprocity [ 75 ], and support services should be sensitive of specific cultural values [ 75 ]. Recent research on a culturally specific face-to-face OSG helped caregivers manage and rethink their caring processes and values [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, whilst assessments were made on socio-economic status, religion and ethnicity, there was limited data provided through the datasets on culture and attitudes to caregiving. Given these may influence the types of activities, frequency and relationship with care recipients, 44 , 45 future assessment in indicated to consider these potentially important factors.…”
Section: Discussionmentioning
confidence: 99%